State Bar Pro Bono Conference in Los Angeles - Watkins, Howard::::::::: (1985)
Toby Rothschild, ?, Leroy Cordova, Patricia Lee and Dan Bradley at luncheon Bradley was Executive Director of the Legal Services Corporation